2021
DOI: 10.1212/nxi.0000000000001024
|View full text |Cite
|
Sign up to set email alerts
|

SARS-CoV-2 Infection in Multiple Sclerosis

Abstract: ObjectiveTo understand COVID-19 characteristics in people with multiple sclerosis (MS) and identify high-risk individuals due to their immunocompromised state resulting from the use of disease-modifying treatments.MethodsRetrospective and multicenter registry in patients with MS with suspected or confirmed COVID-19 diagnosis and available disease course (mild = ambulatory; severe = hospitalization; and critical = intensive care unit/death). Cases were analyzed for associations between MS characteristics and CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
13
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 29 publications
(22 citation statements)
references
References 19 publications
(25 reference statements)
5
13
1
Order By: Relevance
“…Beyond prolonged symptoms, every point of EDSS significantly increased the chance for hospitalization in our cohort. A similar observation was made by other MS centers [37]. The statistical difference in the occurrence of residual symptoms between RRMS and progressive phenotypes of the disease was not significant.…”
Section: Discussionsupporting
confidence: 87%
“…Beyond prolonged symptoms, every point of EDSS significantly increased the chance for hospitalization in our cohort. A similar observation was made by other MS centers [37]. The statistical difference in the occurrence of residual symptoms between RRMS and progressive phenotypes of the disease was not significant.…”
Section: Discussionsupporting
confidence: 87%
“…MS therapy approach during the COVID-19 pandemic has been and still remains a challenge for MS neurologists trying to balance benefits and risks. Prescription of lympho-depleting agents in MS has been a matter of discussion due to the association with COVID-19 susceptibility and outcome risks [ 7 , 29 , 30 ]. Indeed, a survey has recently reported that 23% of centres avoided such therapies, whereas 8% postponed any type of DMD in treatment naïve-patients during the first months of the pandemic [ 25 ].…”
Section: Discussionmentioning
confidence: 99%
“…Of the remaining 114, 7 were selected for the final analysis, along with 6 retrieved out from search strategy (Figure 1). References of 13 selected manuscripts 6,7,9,16,17,18,19,20,21,22,23,24 are shown in Table 1.…”
Section: Resultsmentioning
confidence: 99%